Phytoremediation Potential of Cordyline Fruticosa for Lead Contaminated Soil (Jurnal Pendidikan IPA Indonesia, 2020)
Phytoremediation is a practical, environmentally-friendly, low-cost technological solution used to clean various types of pollution, including metals, pesticide residues, and oils from contaminated soil and water. In this study, Cordyline fruticosa was planted in the lead-contaminated soil. Each pot was given 250 mg/kg and 375 mg/kg of lead. The parameters observed included biomass (mg), lead content in the root, stem, and leaf, bioaccumulation factor, translocation factor, metal tolerance index, and amount of metal extraction, which were analyzed after 30, 60, and 90 days. The results revealed that root, stem and leaf biomass (g) were significantly different from control (T0). The lead contents were rootstem leaf, while the translocation factor value was more than one, except for lead exposure 375 mg/kg (T2) in the second month and 250 mg/kg lead (T1) in the third month. The bioaccumulation factor for all treatments was less than one, and the metal tolerance index ranged from 90.87% - 93.07%. Besides, the amount of root metal extraction was smaller than the shoot. In sum, C. fruticosa is potential phytoremediation.Â